Factors associated with breastfeeding to 3 months postpartum among women with type 1 and type 2 diabetes mellitus: An exploratory study. Issue 3 (May 2020) - Rasmussen, Bodil; Nankervis, Alison; Skouteris, Helen; McNamara, Catharine; Nagle, Cate; Steele, Cheryl; Bruce, Lauren; Holton, Sara; Wynter, Karen
Abstract: Problem: Breastfeeding has significant health benefits for maternal and infant health, yet women with pre-pregnancy diabetes (type 1 or type 2 diabetes mellitus) are often less likely to breastfeed compared with other childbearing women. Background: Intention to breastfeed and making the decision to breastfeed during pregnancy are significant predictors of breastfeeding in the general population, but intention to breastfeed has not been assessed during pregnancy among women with pre-pregnancy diabetes. Aim: To investigate factors associated with breastfeeding to three months postpartum, including demographic, health and reproductive characteristics, perceived support and pre-birth intention to breastfeed, among women with pre-pregnancy diabetes. Methods: A prospective cohort of women with pre-pregnancy diabetes was recruited at three metropolitan hospitals in Melbourne, Australia. Women completed surveys during the third trimester of pregnancy (including intention to breastfeed) and at approximately 3 months postpartum (including current breastfeeding). Factors associated with any breastfeeding at 3 months postpartum were investigated using logistic regression. Findings: Pregnancy surveys were completed by 79 women; three-month postpartum data were available for 47 women. Of these, more than two-thirds (n = 32, 68%) indicated that they were breastfeeding. Controlling for other relevant variables, only pre-birth intention to breastfeed was significantly associated with any breastfeeding at three months (Adjusted Odds Ratio (95% confidence intervals, p) = 20.49 (20.18–20.80, 0.017)). Discussion: Pre-birth intention to breastfeed was the only significant predictor of continued breastfeeding to 3 months postpartum. Conclusion: Pregnancy provides an important opportunity for health professionals to educate and support women with pre-pregnancy diabetes about their breastfeeding intentions.